2017
DOI: 10.1111/1471-0307.12475
|View full text |Cite
|
Sign up to set email alerts
|

An efficient technique for dairy wastewater treatment

Abstract: The aim of this study was to consider the efficiency of the electro‐Fenton process for organic compound reduction in an industrial dairy effluent. Experiments were conducted to evaluate the effect of several parameters, such as reaction time, pH, H2O2/Fe2+ molar ratio and volume fraction of H2O2 to dairy wastewater (mL/L), on the process performance. The Taguchi technique was applied to investigate the optimum operating conditions. The optimum chemical oxygen demand removal (93.24%) was experimentally obtained… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“… Kwapinska & Leahy (2017) investigated the properties of sludge collected from milk processing plants in Ireland and reported that the typical ash content was 36.41% ( Kwapinska & Leahy, 2017 ). The high ash content in the dairy processing sludge is due to the addition of ferric coagulants such as FeCl 3 and FeSO 4 in the wastewater treatment plant reduce the Chemical Oxygen Demand (COD) and Biochemical Oxygen Demand (BOD) levels in dairy wastewater ( Davarnejad et al , 2018 ). This explanation is supported by the high Fe concentration (114422 mg/kg) present in the dairy waste used for HTC experiments.…”
Section: Resultsmentioning
confidence: 99%
“… Kwapinska & Leahy (2017) investigated the properties of sludge collected from milk processing plants in Ireland and reported that the typical ash content was 36.41% ( Kwapinska & Leahy, 2017 ). The high ash content in the dairy processing sludge is due to the addition of ferric coagulants such as FeCl 3 and FeSO 4 in the wastewater treatment plant reduce the Chemical Oxygen Demand (COD) and Biochemical Oxygen Demand (BOD) levels in dairy wastewater ( Davarnejad et al , 2018 ). This explanation is supported by the high Fe concentration (114422 mg/kg) present in the dairy waste used for HTC experiments.…”
Section: Resultsmentioning
confidence: 99%
“…Kwapinska & Leahy (2017) investigated the properties of sludge collected from milk processing plants in Ireland and reported that the typical ash content was 36.41% (Kwapinska & Leahy, 2017). The high ash content in the dairy processing sludge is due to the addition of ferric coagulants such as FeCl 3 and FeSO 4 in the waste water treatment plant reduce the Chemical Oxygen Demand (COD) and Biochemical Oxygen Demand (BOD) levels in dairy wastewater (Davarnejad et al, 2018). This explanation is supported by the high Fe concentration (114422 mg/kg) present in the dairy waste used for HTC experiments.…”
Section: Ash Contentmentioning
confidence: 99%
“…The effluent of this factory contains milk and water used for cleaning, disinfecting, heating, cooling, and washing the floor (Tocchi et al, 2012). The effluent produced depends on factors such as the amount of processed milk, the kind of product and instrument, and the washing way (Davarnejad et al, 2017). The amount and properties of the dairy wastewater depend mainly on the factory size, applied technology, effectiveness, complexity of clean‐in‐place (CIP) methods, good manufacturing practices (GMP), etc.…”
Section: Introductionmentioning
confidence: 99%